Crosstalk between endophytes and a plant host within information-processing networks - Kozyrovska, N.O. (Вiopolymers and Cell, 2013)
Plants are heavily populated by pro- and eukaryotic microorganisms and represent therefore the tremendous complexity as a biological system. This system exists as an information-processing entity with rather complex processes of communication, occurring throughout the individual plant. The plant cellular information-processing network constitutes the foundation for processes like growth, defense, and adaptation to the environment. Up to date, the molecular mechanisms, underlying perception, transfer, analysis, and storage of the endogenous and environmental information within the plant, remain to be fully understood. The associated microorganisms and their investment in the information conditioning are often ignored. Endophytes as plant partners are indispensable integrative part of the plant system. Diverse endophytic microorganisms comprise «normal» microbiota that plays a role in plant immunity and helps the plant system to survive in the environment (providing assistance in defense, nutrition, detoxification etc.). The role of endophytic microbiota in the processing of information may be presumed, taking into account a plant-microbial co-evolution and empirical data. Since the literature are beginning to emerge on this topic, in this article, I review key works in the field of plant-endophytes interactions in the context of information processing and represent the opinion on their putative role in plant information web under defense and the adaptation to changed conditions.